Speculative Attacks and Currency Crises : The Mexican Experience - Otker, Inci.; Pazarbasioglu, Ceyla (Washington, D.C. : International Monetary Fund, 1995)
This paper estimates a speculative attack model of currency crises in order to identify the role of economic fundamentals and any early warning signals of a potential currency crisis. The data from the Mexican economy was used to illustrate the model. Based on the results, a deterioration in fundamentals appears to have generated high one-step-ahead probabilities for the regime changes during the sample period 1982-1994. Particularly, increases in inflation differentials, appreciations of the real exchange rate, foreign reserve losses, expansionary monetary and fiscal policies, and increases in the share of short-term foreign currency debt appear to have contributed to the market pressures and regime changes in that period.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet